Reconciling narrative monetary policy disturbances with structural VAR model shocks? - Martin Kliem; Alexander Kriwoluzky (Deutsche Bundesbank, 2013)
Structural VAR studies disagree with narrative accounts about the history of monetary policy disturbances. We investigate whether employing the narrative monetary shock account as a proxy variable in a VAR model aligns both shock series. We quantify the extent to which the disagreement still applies and identify two explanations for the disagreement. One explanation is measurement error in the narrative time series, another is a misspecification of the VAR model.
Keywords: E31; E32; E52; 330; vector autoregression model; monetary policy shocks; narrative identification